From Exposure to Family Violence During Childhood to Depression in Adulthood: A Path Analysis on the Mediating Effects of Intimate Partner Violence - Chan, Ko Ling (Journal of interpersonal violence, 2021)
Literature shows a link between adverse childhood experiences and subsequent depression, but there is a lack of concrete evidence on whether victimization of intimate partner violence (IPV) in adulthood plays significant roles in that link. This study aimed to test the mediating effect of adulthood IPV victimization in the associations between exposure to family violence in childhood and adulthood depression. Exposure to family violence in childhood was operationalized as one’s experiences of child abuse and witnessing parental IPV in childhood. This study also tested the effects of other violence-related factors from the Personal and Relationships Profile, including one’s antisocial personality, borderline personality, dominance, posttraumatic stress (PTS) symptoms, and violence approval, on the associations. A path analysis was conducted a cross-sectional survey study sample recruited between 2009 and 2010. The sample was 8,807 adults selected with a multistage stratified sampling procedure from six cities in China (43.4% male; M age = 40.61 years, SD = 8.93). The main outcome was participants’ depressive symptoms during the past 2 weeks. As predicted, the path model suggests that IPV victimization significantly mediated the associations between exposure to family violence in childhood and adulthood depression. Violence approval and PTS symptoms, but not the other violence-related factors, significantly mediated the above associations. Findings warrant the need to identify individuals with exposure to family violence in early stages, and to provide them with suitable intervention programs to prevent subsequent IPV as well as to minimize the negative impacts of the exposure to family violence in childhood.